PENGEMBANGAN BUKU AJAR BERORIENTASI PENDIDIKAN KARAKTER PADA MATA KULIAH PEMBELAJARAN PKn SD DI PROGRAM STUDI S1 PGSD - Widya Trio Pangestu (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2014)
Textbooks have become the main element of teaching and learning process. Studies have been conducted to develop instructional materials for the subject of PKn SD at Elementary School Teacher Training Study Program, but there is still limited textbooks with character content, when character have been debating recently. This research is attempetd to develop textbook of PKn SD with character content, by measuring students’ activity, achievement and response. This research is cunducted by class evaluation research method by applying 4-D model. The subjects of the research are 20 students of 5D and 20 of 5I, PGSD-IKIP PGRI Madiun. The results of the research shows that: the learning activity is good by 77.6% of sctive students; 95% of students achieve threshold level by 80.75; textbook is suitable used in average 83.2% and have positive response against the textbook. Keywords: Textbook, character education, PKn SD.